Suppressive effects of Vochysia divergens aqueous leaf extract and its 5-methoxyflavone on murine macrophages and lymphocytes. (15th July 2018) - Corrêa, Maria Fernanda Paresqui; Ventura, Thatiana Lopes Biá; Muzitano, Michelle Frazão; dos Anjos da Cruz, Elaine; Bergonzi, Maria Camilla; Bilia, Anna Rita; Rossi-Bergmann, Bartira; Soares Costa, Sônia
Abstract: Ethnopharmacological relevance: Vochysia divergens Pohl (Vochysiaceae), popularly known as "Cambará", is a tree that is resistant to the seasonal floods in the Pantanal, and usually found in monodominant stands called "Cambarazal". The inhabitants of the Pantanal exploit this tree for medicinal uses. Infusions and decoctions of its leaves are taken as teas, particularly for the treatment of asthma, flu and diarrhea, according to the local tradition transmitted empirically through the generations. Aim of the study: To evaluate the beneficial health effects related to the ethnomedicinal uses of V. divergens (Vd) by using biomonitored fractionation of an aqueous leaf extract. Materials and methods: The aqueous leaf extract was obtained by decoction, and then the extract was fractionated by a combination of separation techniques including precipitation, organic partition and chromatography. Chromatographic analyses of the active samples were carried out using HPLC-DAD-MS. Flavonoid1 was isolated from the n -BuOH fraction through classic chromatographic techniques. The inhibitory effects and cytotoxicity of the Vd extract, fractions and flavonoid1 on NO and TNF-α production were assessed in LPS-stimulated RAW 264.7 macrophage cultures. Additionally, suppression on the proliferation of BALB/c lymphocytes was estimated by [ 3 H] thymidine incorporation. The antioxidant activity of the samples was verified by SNP and DPPH assays and the suppression of the iNOS protein expression was evaluated through Western blotting. Results: The HPLC-DAD-MS analysis of the Vd extract led to the identification of 5-methoxyluteolin-7- O -β-glucopyranoside (2 ), rutin (4 ) and the tannin galloyl-HHDP-glucopyranoside (3 ), besides the main flavonoid 3′, 5-dimethoxyluteolin-7- O -β-glucopyranoside (1 ), which was biologically evaluated in comparison with luteolin aglycone. The Vd extract, n -BuOH fraction and flavonoid1 inhibited NO and TNF-α production by LPS-stimulated macrophages. The reduction of NO levels was mediated mainly by suppression of the i NOS expression. In addition, both the Vd extract (IC50 13.6 µg/mL) and flavonoid1 (IC50 19.8 µg/mL; 41.6 µM) strongly inhibited stimulated lymphocyte proliferation when compared to the immunosuppressive agent cyclosporin A (IC50 43.8 µg/mL; 36.4 µM). The Vd extract also showed a scavenging activity toward DPPH and NO free radicals. This is the first report describing the immunomodulatory potential of V. divergens and its major flavonoid (1 ). Conclusion: Our findings showed that the aqueous leaf extract of V. divergens and its flavonoid reduced the production of excessive pro-inflammatory markers, collaborating with the Pantanal folk medicinal tradition that recommends the tea of cambará leaves for both asthma and flu. In addition, this study contributes to the knowledge of the pharmacological properties of 5-methoxy flavones, a poorly investigated subclass of flavonoids. Graphical abstract: